Hotel Sibir (Tsentralnaya) - Lisitsyn, Vasili (project baikal, 2017)
The article is devoted to the history of construction of the Hotel Sibir in Irkutsk in the hard formative period of the USSR building industry in the 1930s. It reveals the features of the provincial building inhereтt in the hard, but very bright period of domination of the constructivist style.
Keywords: architecture; building; structure; constructivism; hotel